RESILIENCE OF FOLK MEDICINE AMONG THE IGBOS OF SOUTHEAST NIGERIA - Nwankwo, Ignatius Uche (European Scientific Journal, ESJ, 2014)
The purpose of this study is threefold. First is to account for the relevance and resilience of folk medicine among the Igbos of Southeast Nigeria. The second is to find out the level of preference of folk medicine in Igbo society, and thirdly to collate some medical folklores of the Igbo society. Among the Igbos of Southeast Nigeria, folk medicine as a cultural heritage remains one of the bedrock of prevailing health systems despite incursions of orthodox medicine and the effects of globalization, western education and acculturation with other social groups. This research paper employed the cross-sectional survey design. Quantitative and qualitative methods were combined for optimal results. A questionnaire containing eight close ended and two open ended items was administered on 21 0 randomly selected study participants (42 from each state).Data from participant observation involving the researcher and focus group discussions (FGD) with purposively selected male and female groups complemented quantitative data. The Statistical Package for Social Sciences (SPSS) was used for analysis while chi-square test statistics was used to test hypotheses. The findings showed that majority of the respondents accept that folk medicine is relevant (important) in promoting health and safety in the population. It was also found that folk medicine was well preferred by respondents, particularly those with low education. The obvious practical implication of the findings is that folk medicine must not be relegated to the background as is currently the practice in Nigeria. It was recommended that folk medicine be supported by government through adequate funding and research initiatives as well as training of traditional healers. There is also need for co-operation between practitioners of folk medicine and those of orthodox medicine for the greater benefit of society.